Does ESG Performance Drive Long-Term Sustainable Economic Growth in Asia? Insights from a Novel ESG Index and Panel Cointegration Analysis - Thapa, Bharat Singh; Adhikari, Bibek; Pathak, Durga Datt (Nepal Journal of Multidisciplinary Research, 2025)
Background: Rapid population growth and the depletion of natural resources pose significant global challenges. These issues are further exacerbated by unethical corporate practices, such as accounting fraud and financial scandals, which contribute to economic downturns. This study investigates the role of Environmental, Social, and Governance (ESG) performance in fostering sustainable economic growth in Asia. Methods: This study adopts an explanatory research design, utilizing panel data collected from the World Bank for 46 Asian countries spanning the period from 1990 to 2022. The causality was determined using a robust panel regression model to examine the long-term and short-term effects of ESG performance on economic growth. Results: The findings reveal a strong positive long-term relationship between ESG performance and GDP per capita, suggesting that sustainable practices enhance productivity, attract investment, and contribute to human capital development. However, short-term effects are largely insignificant, except in specific Asian countries where targeted policies and rapid transitions yield immediate benefits. Conclusion: The study underscores the critical role of ESG performance in driving long-term sustainable economic growth in Asia. It highlights clear long-term benefits, including increased productivity, investment, and human capital development, despite limited short-term effects in certain regions. These findings emphasize the need for policymakers and stakeholders to integrate ESG criteria alongside financial metrics, enabling them to enhance economic resilience, drive innovation, improve financial performance, and address environmental and social challenges. Novelty: This research creates novelty by contributing in three ways. First, it develops a unique ESG index in the absence of a standardized ESG index for Asian countries. Second, while most existing studies focus on the impact of ESG adoption on firm-level performance, this study shifts the perspective to a macroeconomic scale, examining how ESG performance influences overall economic growth. Thirdly, it provides empirical evidence on the impact of ESG performance on economic growth in the region, offering valuable insights for sustainable development policies.